MEASLES-MUMPS-RUBELLA VACCINATION IN A PAEDIATRIC TRANSPLANT PATIENT USING EVEROLIMUS - Aybüke Kaçır; Övgü Büke; Nalan Karabayır; Mine Başıbüyük; Demet Deniz Bilgin; Özlem Öcal (İstanbul Tıp Fakültesi Dergisi)
There is limited information regarding the administration of live vaccines to paediatric transplant patients who are at increased risk of infection. A 7-year-old liver transplant patient who had everolimus therapy was evaluated for Measles-Mumps-Rubella (MMR) vaccination. After checking the lymphocyte count, immunoglobulin G, and serum everolimus levels, the MMR vaccine was administered. No side effects were observed during follow-up, and the antibody levels were found to be positive after two months. This article presents a case of paediatric solid organ transplantation patient who received a measles-mumps-rubella vaccination while receiving immunosuppressive everolimus therapy.